Variability of residue concentrations of ciprofloxacin in honey from treated hives. Issue 4 (3rd April 2017) - Chan, Danny; Macarthur, Roy; Fussell, Richard J.; Wilford, Jack; Budge, Giles
ABSTRACT: Honey bees ( Apis mellifera L.) were treated with a model veterinary drug compound (ciprofloxacin) in a 3-year study (2012–14) to investigate the variability of residue concentration in honey. Sucrose solution containing ciprofloxacin was administered to 45 hives (1 g of ciprofloxacin per hive) at the beginning of the honey flow in late May/mid-June 2012, 2013 and 2014. Buckfast honey bees ( A. mellifera – hybrid ) were used in years 2012 and 2013. Carniolan honey bees ( A. mellifera carnica ) were used instead of the Buckfast honey bees as a replacement due to unforeseen circumstances in the final year of the study (2014). Honey was collected over nine scheduled time points from May/June till late October each year. Up to five hives were removed and their honey analysed per time point. Honey samples were analysed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) to determine ciprofloxacin concentration. Statistical assessment of the data shows that the inter-hive variation of ciprofloxacin concentrations in 2012/13 is very different compared with that of 2014 with relative standard deviations (RSDs) of 138% and 61%, respectively. The average ciprofloxacin concentration for 2014 at the last time point was more than 10 times the concentration compared with samples from 2012/13 at the same time point. The difference between the 2012/13 data compared with the 2014 data is likely due to the different type of honey bees used in this study (2012/13 Buckfast versus 2014 Carniolan). Uncertainty estimates for honey with high ciprofloxacin concentration (upper 95th percentile) across all hives for 55-day withdrawal samples gave residual standard errors (RSEs) of 22%, 20% and 11% for 2012, 2013 and 2014, respectively. If the number of hives were to be reduced for future studies, RSEs were estimated to be 52% (2012), 54% (2013) and 26% (2014) for one hive per time point (nine total hives).